Habitat of mammals in West Java, Indonesia - ERRI N. MEGANTARA; Sya Sya Shanida; TEGUH HUSODO; PUPUT FEBRIANTO; M. PAHLA PUJIANTO; RANDI HENDRAWAN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Megantara EN, Shanida SS, Husodo T, Febrianto P, Pujianto MP, Hendrawan R. 2019. Habitat of mammals in West Java, Indonesia. Biodiversitas 20: 3380-3390. West Java has various habitat types, natural forests and human-land modified. Based on previous studies by Padjadjaran University that mammals were found in several locations, such as Gunung Salak, Ciletuh, Cisokan, Kamojang, and Darajat. There are many mammals found in various habitat so that it is important to reveal the habitat types that are usually used by mammals to fulfill their daily needs. The purpose of this study is to reveal the habitat types that are most commonly found in mammal species. Semi-structured interviews, direct observations, camera trapping, sign survey, and collapsible trap installation were applied in this study. Based on the results of the study, Mammals in West Java were found in 54 species, 21 families, and nine orders. Natural forests found 38 species, while mammals found in human-land modified as many as 16 species. In human land modified, agroforestry found more mammal species compared to other human-land.